Design and performance analysis of a charge controller for solar system using MATLAB/SIMULINK - Samuel, Isaac A.; Izi, Oghenekome; Somefun, Tobiloba E.; Awelewa, Ayokunle A.; Katende, James (Frontiers in Energy Research, 2022)
The energy utilization of the PV modules is based on their ability in extracting maximum power and it is highly dependent on the type of maximum power point tracking (MPPT) algorithm used. The Perturb and Observe algorithm is the most widely researched and used among the many developed algorithms. Using this algorithm with a definite duty cycle introduces certain drawbacks to the system such as low efficiency and irregular output oscillations. This study aims to eliminate these drawbacks by introducing a voltage referencing set up as a PI controller. It accepts the reference voltage and current and then converts them into a redefined duty cycle suitable enough to power the transistor and in general control the proposed model. Using the MATLAB/SIMULINK simulation tool, the result shows that by incorporating the PI controller into the system, the efficiency of 99.96% at the maximum power point was attained. Hence, the PI controller plays a significant role in improving the efficiency and reliability of the Perturb and Observe algorithm by producing an output voltage at regular oscillation safe to charge batteries and power loads.